2016
DOI: 10.1158/1535-7163.mct-15-0871
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Activity of AMG 337, a Potent and Selective MET Kinase Inhibitor, in MET-Dependent Cancer Models

Abstract: The MET receptor tyrosine kinase is involved in cell growth, survival, and invasion. Clinical studies with small molecule MET inhibitors have shown the role of biomarkers in identifying patients most likely to benefit from MET-targeted therapy. AMG 337 is an oral, small molecule, ATP-competitive, highly selective inhibitor of the MET receptor. Herein, we describe AMG 337 preclinical activity and mechanism of action in MET-dependent tumor models. These studies suggest MET is the only therapeutic target for AMG … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 37 publications
0
54
1
Order By: Relevance
“…The association between MET amplification and a poor prognosis in gastroesophageal cancer has also been confirmed in a recent meta-analysis (4,10). Beside the prognostics characteristics it has been suggested that MET amplification in gastroesophageal cancer potentially possess predictive properties in relation to Met targeted therapy and, thereby, could act as a companion diagnostic for some of the new therapies under development (3,11). Furthermore, in nonsmall cell lung cancer it has been suggested that MET amplification is involved with acquired resistance to EGFR tyrosine kinase inhibitors (12,13).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The association between MET amplification and a poor prognosis in gastroesophageal cancer has also been confirmed in a recent meta-analysis (4,10). Beside the prognostics characteristics it has been suggested that MET amplification in gastroesophageal cancer potentially possess predictive properties in relation to Met targeted therapy and, thereby, could act as a companion diagnostic for some of the new therapies under development (3,11). Furthermore, in nonsmall cell lung cancer it has been suggested that MET amplification is involved with acquired resistance to EGFR tyrosine kinase inhibitors (12,13).…”
Section: Introductionmentioning
confidence: 81%
“…These specimens were collected consecutively from the screen population related to a phase II study with the investigational Met tyrosine kinase inhibitor AMG337 (Amgen, Thousand Oaks, CA, USA) (11). All specimens were anonymized with respect to the identity of the patients and no data on patient demographic was available.…”
Section: Specimensmentioning
confidence: 99%
“…In many studies, it has been reported that overexpression of HGF and c-MET contributes to resistance to other therapies, such as TKIs targeting EGFR, BRAF, and HER2, as well as chemotherapy and radiotherapy (21,28). Therefore, HGF-c-MET-targeting therapies have emerged as attractive strategies, and a large number of clinical trials involving c-MET TKIs are ongoing (10,25,28). However, in the case of c-MET TKIs, the inhibitory effect is valid only in cells harboring constitutively activated c-MET (26,29).…”
Section: Discussionmentioning
confidence: 99%
“…Among c-MET-negative gastric cancer cell lines, IM95 cells are sensitive to c-MET TKIs (10). This is because IM95 cells have high expression of HGF, which triggers c-MET activation in an autocrine manner and responses to c-MET TKIs (10,30). In this study, the effect of altered HGF expression on c-MET inhibition was analyzed in terms of functional significance in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…AMG 337 is a highly selective small-molecule MET inhibitor that blocks MET kinase activity (18,19). AMG 337 selectively inhibits the proliferation of MET-amplified tumor cell lines, inhibits HGFinduced MET phosphorylation and Gab-1 phosphorylation in METdependent tumor models, and reduces tumor xenograft growth in MET-amplified gastric cancer models (18,19).…”
Section: Introductionmentioning
confidence: 99%